Niemieckie zbrodnie nazistowskie w Lesie Lućmierskim w świetle badań etnoarcheologicznych - Ławrynowicz, Olgierd; Badji, Justyna; Majewski, Maciej (Acta Universitatis Lodziensis. Folia Archaeologica, 2018)
For several years, regular archaeological excavations have been conducted in the Forest of Lućmierz near Zgierz in Central Poland. They focused on searching for the collective graves of hundreds Poles executed by Nazi Germans in Zgierz in 1942, and the location and exhumation of the contents of burial graves from 1939–1940, in which the remains of victims of the German Inteligenzaktion were originally hidden. In both cases, the main difficulty for the researchers was the fact that the Germans carried out actions to erase the traces of the crime, consisting in the cremation of the remains of the victims extracted from the grave. Unclear information regarding exhumations, which was provided by the new Polish administration in the spring of 1045, did not facilitate the research either. The archival inquiry and archaeological research did not answer all the questions. Therefore, in 2014, some ethnographic interviews with the residents of the towns located around the Forest of Lućmierz were carried out. The article cites extensive fragments of the interlocutors’ statements, which have been commented on from the point of view of the needs of the archaeological research.